Developing Conceptual Design of Slab Structure Parametric Variations Shophouses using Value Engineering Concept - Nadia Diandra; Stephen Valentino Lie; Adianto Wicaksono (Universitas Medan Area, 2023)
Along with the development of technology, the decision in choosing the implementation method is the main key in construction projects. This is because the implementation method will affect the elements of construction, namely cost, time and quality or what is known as the triple constraint theory. Therefore, the development of construction projects is required to realize construction methods that are economical in terms of cost and efficient in terms of work. This research was carried out by structural analysis to obtain the design or planning of various variations of the optimal structure. Next, calculate the cost of floor slab work using the components of the work volume and the unit price of the work. Time analysis was carried out to determine the duration of the overall implementation of each construction method using the PDM (Precedence Diagram Method) scheduling method with Microsoft Excel tools. From the results of the analysis, it was found that the cheapest floor slab cost was a variation of three types of bondek slabs with an efficiency of 14% compared to variations of one type of conventional slab. Meanwhile, the fastest floor slab work execution time is a variation of three types of hollow core slabs with an efficiency of 31% compared to variations of one type of conventional slab.